2021
DOI: 10.1108/ijis-10-2020-0178
|View full text |Cite
|
Sign up to set email alerts
|

Values, satisfaction and intentions: online innovation perspective for fashion apparels

Abstract: Purpose The purpose of this study is to survey the associations among innovation perspective on value priorities, i.e. hedonic vs utilitarian facets, satisfaction among customers and behavioral intents for online fashion apparels in the Asian economic context, i.e. Indian market. Design/methodology/approach The research used a hypo-deductive strategy and all the constructs were amended from the previous scholarly work. The two-step methodology with structural equation modelling in terms of covariance-based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 141 publications
(152 reference statements)
0
11
0
2
Order By: Relevance
“…First, a plethora of research has explored SMMA in a variety of contexts ( Kautish and Sharma, 2019 ; Khare and Kautish, 2020 ). There is a severe dearth of studies with mediating and moderation relationship of SMMA ( Kautish et al, 2021a ). SMMA needs to be studied in the context of online shopping B2C e-commerce websites (e.g., Facebook, Instagram, and WhatsApp), which are gaining popularity in today’s emerging market ( Kautish et al, 2021d ).…”
Section: Introductionmentioning
confidence: 99%
“…First, a plethora of research has explored SMMA in a variety of contexts ( Kautish and Sharma, 2019 ; Khare and Kautish, 2020 ). There is a severe dearth of studies with mediating and moderation relationship of SMMA ( Kautish et al, 2021a ). SMMA needs to be studied in the context of online shopping B2C e-commerce websites (e.g., Facebook, Instagram, and WhatsApp), which are gaining popularity in today’s emerging market ( Kautish et al, 2021d ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study also found that the direct effect of consumers' perceptions of organizational use of mobile media in gratification, intimidation, promotion, and organizational example is positively related to consumer intentions. The company's strength in controlling intentions by influencing consumer perceptions and attitudes to make sales (Schniederjans et al 2018) Research has focused on the utilitarian motivation of buyers and oriented behaviors defined as functional, work-related, or task-oriented (Kautish et al 2021).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Based on the figure below, it can be seen that six hypotheses have a positive relationship (H1, H2, H3, H4, H6, and H7), one hypothesis has a significant negative relationship (perception of consumers on Furthermore, when sharia products are increasingly adding to the Islamic image that consumers want. The repercussions can increase consumers' intention to use sharia products continuously because consumers find a match between themselves and Sharia products (Fox et al 2018;Jeong & Jang, 2018;Shin, 2020) or because they feel the benefits derived from sharia products (Kautish et al 2021). Furthermore, consumers who believe in sharia values so that complete information on sharia products related to conformity with religious guidance.…”
Section: Structural Model Testmentioning
confidence: 99%
“…They describe two critical dimensions in this regard: one is traditional car rental and the other is m-rental which is not explored in the existing literature. The 12th paper in this special issue is titled "Values, satisfaction and intentions: Online innovation perspective for fashion apparels" by Kautish et al (2021). The paper reveals that utilitarian and hedonic values as value priorities significantly affect customer satisfaction, which in turn impacts the behaviour of customers' intention for fashion apparel on the online platform.…”
Section: The Focus Of the Special Issuementioning
confidence: 99%